Primary extranodal diffuse large B-cell lymphoma in the rituximab era: a single center, retrospective analysis. Issue 1 (31st December 2022) - Zhao, Jinrong; Zhang, Wei; Zhou, Daobin
ABSTRACT: Objectives: To analyse the clinical characteristics and therapeutic response of Chinese patients with primary extranodal diffuse large B-cell lymphoma DLBCL (PE-DLBCL). Methods: We analysed the clinical features and outcomes of 197 patients who were newly diagnosed with PE-DLBCL between January 2015 and December 2020. Results: The gastrointestinal tract showed the highest rate of involvement (34%), followed by the central nervous system (CNS) and intraocular system (31.5%). The 3-year overall survival (OS) rate was 81% for the entire group and 79% for those with CNS and vitreoretinal involvement. Ann Arbour stage, lactate dehydrogenase level, International Prognostic Index > 2, and complete remission (CR) were significantly related to the survival of patients with PE-DLBCL. The lack of CR was the only independent adverse prognostic factor for OS. Conclusion: The clinical outcomes of patients with PE-DLBCL at our centre were encouraging, especially for patients with CNS and vitreoretinal involvement.